2001
DOI: 10.1109/35.920862
|View full text |Cite
|
Sign up to set email alerts
|

Management of quality of service enabled VPNs

Abstract: New emerging IP services based on differentiated services and the IP security architecture offer the level of communication support that corporate Internet applications need nowadays. However, these services add an additional degree of complexity to IP networks which will require sophisticated management support. The management of enhanced IP services for their customers is thus an emerging important task for Internet service providers. This article describes a potential management architecture service provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2003
2003
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Some of such characteristics have been identified as determinants of IB-adoption propensities, including customers' level of involvement with the internet and other banking technologies (see Lassar et al, 2005;Floh and Treiblmaier, 2006;Maenpaa et al, 2008;Polasik and Wisniewski, 2009). Others include risk perception and level of risk acceptance (Chung and Paynter, 2002;Berger and Gensler, 2007;Srivatsa and Srinivasan, 2007;Aldas-Manzano et al, 2009), variety seeking behaviour (Magi, 2003;Srivatsa and Srinivasan, 2007), desire to control service delivery (Ramsay and Smith, 1999;Braun et al, 2001;Henry, 2005), and willingness/ reluctance to accept changes in service delivery (Suganthi et al, 2001;Sohail and Shanmugham, 2003). Srivatsa and Srinivasan (2007) also conceptualised changereluctance as "inertia for change" and found that it was a major influencer of IB-channel choices in India.…”
Section: Customer Attitudes and Psychographics And Ib Adoptionmentioning
confidence: 99%
“…Some of such characteristics have been identified as determinants of IB-adoption propensities, including customers' level of involvement with the internet and other banking technologies (see Lassar et al, 2005;Floh and Treiblmaier, 2006;Maenpaa et al, 2008;Polasik and Wisniewski, 2009). Others include risk perception and level of risk acceptance (Chung and Paynter, 2002;Berger and Gensler, 2007;Srivatsa and Srinivasan, 2007;Aldas-Manzano et al, 2009), variety seeking behaviour (Magi, 2003;Srivatsa and Srinivasan, 2007), desire to control service delivery (Ramsay and Smith, 1999;Braun et al, 2001;Henry, 2005), and willingness/ reluctance to accept changes in service delivery (Suganthi et al, 2001;Sohail and Shanmugham, 2003). Srivatsa and Srinivasan (2007) also conceptualised changereluctance as "inertia for change" and found that it was a major influencer of IB-channel choices in India.…”
Section: Customer Attitudes and Psychographics And Ib Adoptionmentioning
confidence: 99%
“…2, three elements are required to implement the aforementioned dynamic resource allocation scheme: a Traffic Measurement and Prediction algorithm (TMP), a dynamic resource allocation algorithm or Rate Calculation (RC) and a Resource Reservation technique (RR). For TMP, the exponentially weighted moving average algorithm [ 1] is applied and for RR Customer Queue (CQ) [7] is employed in the architecture. The resource calculation algorithm (RC) is the emphasis of this paper, and the aggregated traffic based packet loss estimation formula is applied [6].…”
Section: Architecture and Algorithm Descriptionmentioning
confidence: 99%
“…Presently, the implementation of IP/MPLS based VPN services [1] became a profitable market for Network Service Providers (NSPs), due to a larger Return on Investment (ROI) as compared to the original access service. QoS is one of the key issues to decide customers' satisfaction and affect purchasing decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [7][8][9] make best use of the substrate network resources based on heuristic approaches, without considering the reliability of VNs issue under substrate node or link failures, so these studies cannot provide VN with capabilities of failure recovery. Besides, the studies in context of VPN [11] and WDM networks [12] also extensively investigate the problem of reliability-guaranteed network resource allocation, while these works are only considered the links constrains. However, there are both constraints on the nodes and the links in context of VN mapping.…”
Section: Introductionmentioning
confidence: 99%